Radical Spiritual Motherhood : Autobiography and Empowerment in Nineteenth-Century African American Women - Haynes, Rosetta Renae (Book collections on Project MUSE., 2010)
In this cutting-edge work, Rosetta R. Haynes explores the spiritual autobiographies of five nineteenth-century female African American itinerant preachers to discover the ways in which they drew upon religion and the material conditions of their lives to fashion powerful personas that enabled them to pursue their missions as divinely appointed religious leaders. Haynes examines the lives and narratives of Jarena Lee (1783-?), Zilpha Elaw (c. 1790-?), Julia Foote (1823-1900), Amanda Berry Smith (1837-1915), and Rebecca Cox Jackson (1795-1871) through an innovative conceptual framework Haynes.